Periplaneta americana extract (L.) promotes hair regrowth in Alopecia areata mice by reducing inflammation and modulating skin microbiota - Guan, Tangfei; Yang, Xin; Hong, Canhui; Zhu, Jiali; Xiao, Peiyun; Yang, Yongshou; Zhang, Chenggui; He, Zhengchun (Frontiers in Pharmacology, 2025)
IntroductionAlopecia areata (AA), an autoimmune hair-loss disease due to follicular inflammatory cell infiltration, lacks an ideal cure. The Periplaneta Americana (PA) extract (PA-011), a traditional Chinese medicine with anti-inflammatory, antioxidant, tissue-repair-promoting, and immune-regulating properties, was studied for its AA-treating effects.MethodsGuided by network pharmacology, AA model mice were treated with PA-011. Hair growth, skin tissue, inflammatory factors, and Wnt protein levels were examined. Transcriptomics, metabolomics, and 16S rRNA sequencing explored the hair-growth-promoting mechanisms.ResultsNetwork pharmacology showed PA-011 could regulate AA-related targets and pathways. PA-011 intervention promoted hair follicle cell proliferation and hair growth in AA mice, reduced skin TNF-α, IL-23, and VCAM-1 expression. Transcriptomics and WB analysis indicated PA-011 downregulated inflammatory genes, activated Wnt3a, and modulated the TGF-β pathway. Metabolomics found PA-011 regulated metabolic pathways. 16S rRNA analysis showed it reversed AA-induced skin microbiota changes, inhibiting pathogens and promoting probiotics. Multi-omics analysis revealed PA-011 regulated skin microbiota and metabolic balance for hair growth.DiscussionIn conclusion, PA-011 alleviates AA by reducing skin inflammation and modulating skin microbiota, suggesting its potential as an AA therapeutic.